Thermal Stability of PS-PVD YSZ Coatings with Typical Dense Layered and Columnar Structures - Zefei Cheng; Jiasheng Yang; Fang Shao; Xinghua Zhong; Huayu Zhao; Yin Zhuang; Jing Sheng; Jinxing Ni; Shunyan Tao (Crystals, 2020)
Yttria-stabilized zirconia (YSZ) coatings with typical pyramid columnar and dense layered structure were prepared by plasma spray-physical vapor deposition (PS-PVD). The evolution behavior of microstructure and crystallography of the coatings before and after thermal aging treatment were observed by electron backscatter diffraction (EBSD) and field emission scanning electron microscopy (FE-SEM). Results showed that the as-deposited coatings exhibited many types of structures and were mainly composed of a nonequilibrium tetragonal (t’-ZrO2) phase. With the prolonging of thermal exposure time, the initial nonequilibrium tetragonal phase of YSZ coatings gradually transformed into a monoclinic (m-ZrO2) phase. During the process of stationary deposition, at a proper spraying distance, each column exhibited a certain preferred orientation, but the ceramic topcoat did not exhibit distinct preferred orientation statistically.